Improved speech enhancement based on spectral subtraction and auditory masking effect - ZHAO Xiao-qun; HUANG Xiao-shan (Tongxin xuebao)
Taking into account the masking properties of human auditory system and the uncertainty of the speech pres-ence,the novel algorithm modifies the log-spectral amplitude estimation and the speech absence probability（SAP） pa-rameter.Then,the smoothing parameters in noise estimation and prior SNR estimation are adaptively adjusted to modi-fied SAP parameter which reflects the degree of stationary of the measured signal.The change of smoothing parameters allows for automatic adaptation with various noisy environments and obtains the best trade-off.Experimental results demonstrate that the proposed algorithm has better performance of speech articulation without any perceptional musical-ity,compared to another modified spectral subtraction algorithms under the same level of noise reduction,and this supe-riority is more significant at very low SNR.